244224 On delayed technological objects and their characteristics - Ikromjonova, Nodira; Qodirov , Dilmurod (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
This article provides information about delayed objects, the causes of their delay and methods of reducing their delay time.